Creation of the normative-legal framework preschool of education of Ukraine (2000-2012 years) (Pedagogy of Higher and Secondary Education, 2013)
Haran N. S. Creation of the normative-legal framework preschool of education of Ukraine (2000-2012 years).Article continues the series of publications of the author on the study of the development of pre-school education system of Ukraine. The purpose of the proposed article, the author sees in fact, to present the issues of normative-legal support of pre-school education of Ukraine. The author tries to in chronological sequence to consider the stages of creation of the legal base of pre-school education of Ukraine for 2000-2012 years.
Keywords: the system of pre-school education; children’s garden; the normative-legal base; training of the educational process; pre-school education